Right Compared With Left Thoracic Approach Esophagectomy for Patients With Middle Esophageal Squamous Cell Carcinoma - Zheng, Yan; Li, Yin; Liu, Xianben; Zhang, Ruixiang; Sun, Haibo; Xing, Wenqun (Frontiers in Oncology, 2020)
Background: In China, open surgical approaches for esophageal cancer (EC) can be divided into two techniques, the right- and left- transthoracic esophagectomy. Although there is an increasing number of instances that use the right side, the optimal surgical technique remains unclear. Based in a large cancer center with rich experience of both transthoracic side approaches, this study compared the long-term survival of patients treated by these two surgical techniques. Methods: The patients included in this study underwent a right transthoracic esophagectomy (Right, McKeown) or left transthoracic esophagectomy (Left, Sweet, or chest neck dual-incision) for esophageal squamous cell carcinoma (ESCC) between January 2015 and October 2018. The overall survival(OS) rate and perioperative data between the two groups were then retrospectively analyzed. Results: We included 437 patients who underwent Right (n = 202) and Left (n = 235) approaches for ESCC. There was a significantly longer median operative time (250 vs. 190 min, P < 0.001) and longer median postoperative hospital stay (17 vs. 14 days, P < 0.001) in the Right side group. The OS at 5-years was 49.9% in the Right group and 52.45% in the Left group; hazard ratio (HR) (95% CI): 1.002 (0.752–1.337), p = 0.987. Conclusions: For middle thoracic ESCC without suspected lymph node metastasis in the upper mediastinum, the esophagectomy through the Left thoracic approach could achieve the same OS as the Right side, with better short-term outcomes.